Traditional Chinese Medicine Constitution Types and Apolipoprotein B in Hyperuricemia: Associations with Cardiovascular Risk: TCM Types and Apo B in Hyperuricemia - Yang, Shuo; Li, Jinfeng; Zeng, Hongli; Zhang, Xueping; Xiong, Deliang; Tang, Wenyi; Sun, Bin; Yu, Peng; He, Xiaohong; Zhang, Weizheng (Journal of Medical Biochemistry, 2025)
Background: To explore the correlation between different traditional Chinese medicine (TCM) constitution types and apolipoprotein B (ApoB) in patients with hyperuricemia (HUA), and to investigate the relationships between TCM constitutions, uric acid levels, and various cardiovascular risk factors. Methods: A cross-sectional study involving 683 patients diagnosed with HUA was conducted. Patients’ TCM constitutions were classified using the standardized "Classification and Determination of TCM Constitution" questionnaire. Serum uric acid (UA), lipid profiles, ApoB, and homocysteine (Hcy) levels were measured. Results: Among 683 HUA patients, phlegm-dampness (22.99%) and damp-heat constitution (20.06%) were the most common TCM constitution types. UA, ApoB, and Hcy levels in patients with phlegm-damp constitution were significantly higher than those in other constitutions (P<0.05). UA levels were negatively correlated with HDL-C (r=-0.472, P=0.027) and positively correlated with ApoB (r=0.618, P=0.012), and Hcy (r=0.492, P=0.018). Male gender, BMI, ApoB, Hcy, and phlegm-dampness constitution are independent factors associated with UA levels. Patients with high ApoB levels had a significantly higher incidence of cardiovascular diseases compared to those with low ApoB levels (male: 42.73% vs 22.81%, P<0.001; female: 37.82% vs 25.21%, P=0.036). Logistic regression analysis revealed that phlegm-dampness constitution (OR=2.18, 95% CI: 1.42-3.35, P<0.001) and damp-heat constitution (OR=1.86, 95% CI: 1.21-2.87, P=0.005) were independently associated with increased risk of cardiovascular diseases. Conclusion: Phlegm-damp and damp-heat constitutions are the most common TCM constitution types in HUA patients and are associated with higher levels of UA, ApoB, and Hcy. These constitution types are independently associated with increased cardiovascular risk.